Pengaruh Struktur Kepemilikan, Intensitas Modal, dan Likuiditas Terhadap Tax Avoidance Pada Perusahaan Sektor Teknologi - Lenni Milandini; Pujo Gunarso (STIE PGRI Dewantara Jombang, 2026)
Tax avoidance is a strategy or method used by companies to avoid or reduce corporate taxes legally. The purpose of this study is to analyze the effect of ownership structure, capital intensity, and liquidity on tax avoidance in technology sector companies listed on the Indonesia Stock Exchange for the period 2022-2024. The quantitative method used was secondary data in the form of company annual reports for the period 2022-2024. Using a purposive sampling method, 13 companies met the established criteria. The results show that ownership structure has no effect on tax avoidance, capital intensity has a negative effect on tax avoidance, and liquidity has no effect on tax avoidance. The conclusion is that institutional shareholders do not prioritize oversight, and the higher the level of fixed asset ownership, the higher the level of tax avoidance. Furthermore, the higher the level of liquidity used for tax avoidance.